Investigating Factors that affecting the Continued use of Internet Banking: Case Study of Libya - Rfieda, Ali (Information Management and Business Review, 2013)
After technological progress and in particular the development of internet, internet banking service has intensified the competition between banks as well as allowed customers to easily compare the services that provided by different banks. While the goal of any business entity in the long term is to increase its productivity and maximisation of the profits, customer retention becomes an important component of banking strategy in today’s increasingly competitive environment to foster customer relationship management. In order to achieve this, it is important to concentrate on the consumer’s continued use of a service rather than solely on their acceptance of the service (Adapa, 2011). Therefore, understanding the importance of consumers’ continued use is the key element to maximise customers’ retention in internet banking services.